Usefulness of the Total Thrombus‐Formation Analysis System (T‐TAS) in the diagnosis and characterization of von Willebrand disease. (13th June 2016) - Daidone, V.; Barbon, G.; Cattini, M. G.; Pontara, E.; Romualdi, C.; Di Pasquale, I.; Hosokawa, K.; Casonato, A.
Abstract : Introduction: The heterogeneity of von Willebrand disease (VWD) makes its diagnosis a difficult task. Methods: We report here on the usefulness of a microchip‐based flow‐chamber system, the total thrombus‐formation analysis system (T‐TAS), in the identification and characterization of VWD. Thirty VWD patients and 20 healthy subjects were studied with the T‐TAS platelet (PL) and atherome (AR) microchips developed for the in vitro assessment of platelet thrombus formation and fibrin‐rich platelet thrombus formation respectively. Results: Samples from severe type 1 VWD, characterized by von Willebrand factor (VWF) levels below 10 U dL −1, failed to occlude either the PL or the AR chip capillaries, while the occlusion times were normal in patients with mild type 1 VWD (VWF above 25 U dL −1 ). PL and/or AR chip occlusion occurred, but took longer than normal, for samples from type Vicenza and type 1 VWD patients, whose VWF levels ranged between 10 and 25 U dL −1 . No PL or AR chip capillary occlusion was seen for samples from patients with type 2A or 2B VWD featuring the absence of large VWF multimers, whereas no abnormalities emerged for type 2B patients with normal multimer patterns. Conclusion: The T‐TAS appears to be sensitive mainly to plasma VWF concentration and the presence of large multimers. Failure of the PL and AR chips to become occluded points to a lack of large VWF multimers, or type 1 VWD with VWF levels below 10 U dL −1 . Although the T‐TAS does not assure a precise VWD diagnosis, it does point us in the right direction, and thus seems a useful global preliminary test.